Method for preparing silicon monoxide using quartz crucible waste

CN122940175APending Publication Date: 2026-10-20KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611361572.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种利用石英坩埚废料制备氧化亚硅的方法,以解决现有技术中石英坩埚废料无法处理、污染环境的问题

Benefits of technology

本发明通过将光伏行业产生的石英坩埚废料转化为高附加值的氧化亚硅材料,变废为宝,有效缓解废坩埚堆存带来的环境压力,可同步消化光伏硅切割废料,实现多种光伏固废的协同资源化利用,同时各步骤操作条件成熟,设备通用性强,适合规模化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention provides a method for preparing silicon suboxide from quartz crucible waste, belonging to the field of photovoltaic solid waste resource utilization technology. The quartz crucible waste is crushed, ground, and sieved to obtain quartz crucible powder; the quartz crucible powder is then acid-washed to remove impurities, yielding silica powder; finally, the silica powder and pure silicon powder are mixed and subjected to a disproportionation reaction and cooling to obtain silicon suboxide. This invention transforms quartz crucible waste generated in the photovoltaic industry into high-value-added silica material, turning waste into treasure, effectively alleviating the environmental pressure caused by the accumulation of waste crucibles, simultaneously utilizing photovoltaic silicon cutting waste, and achieving the synergistic resource utilization of various photovoltaic solid wastes. Furthermore, the operating conditions for each step are mature, the equipment is highly versatile, and it is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photovoltaic solid waste resource utilization technology, and in particular to a method for preparing silicon suboxide using quartz crucible waste. Background Technology

[0002] Quartz crucibles are essential containers in the casting of polycrystalline silicon ingots and the pulling of monocrystalline silicon for photovoltaic applications. They are used to hold molten silicon at high temperatures of approximately 1450–1550°C. Due to crystallization, deformation, and even breakage after prolonged use, quartz crucibles cannot be recycled, and their lifespan is typically only 200–500 hours. With the continuous expansion of photovoltaic industry capacity, the amount of waste quartz crucibles generated is increasing year by year. A large amount of waste is mainly disposed of through landfills and stockpiles, which not only increases production costs for enterprises but also creates environmental pollution pressure from solid waste.

[0003] Currently, the resource utilization pathways for waste quartz crucibles are relatively limited. There are reports of using them to prepare materials such as silicon-based electrical porcelain and mullite whiskers, and attempts have been made to recover high-purity fused quartz through methods such as acid washing and high-temperature melting. However, these utilization methods have low added value and fail to fully utilize the high-purity silica value advantage of quartz crucible waste.

[0004] Silicon suboxide (SiO) is a key precursor for high-capacity anode materials in lithium-ion batteries and can also be used to prepare functional materials such as optoelectronic thin films and vapor-deposited materials. Traditional SiO preparation methods use elemental silicon powder and silica powder as raw materials, generating SiO gas through a disproportionation reaction under high-temperature vacuum conditions, which is then condensed and collected. If waste quartz crucibles can be used instead of high-purity quartz sand as the silicon source, combined with elemental silicon, high-value recycling of waste materials can be achieved, significantly reducing raw material costs. While there are reports of using diamond wire cutting waste slurry to prepare SiO, there is currently no technical solution specifically using waste quartz crucibles as the primary silicon source for SiO preparation. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing silicon suboxide using quartz crucible waste, so as to solve the problem of the inability to process quartz crucible waste and the resulting environmental pollution in the prior art.

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing silicon suboxide using quartz crucible waste, comprising the following steps: (1) The quartz crucible waste is crushed, ground and sieved to obtain quartz crucible powder; (2) The quartz crucible powder is acid-washed to remove impurities, and silicon dioxide powder is obtained; (3) After mixing silica powder and pure silicon powder, disproportionation reaction is carried out and then cooled to obtain silicon suboxide.

[0007] Preferably, in step (1), the particle size of the quartz crucible powder is 2~5μm.

[0008] Preferably, in step (2), the acid washing and impurity removal process is carried out by soaking in an acid solution, wherein the acid solution includes one or more of hydrochloric acid solution, sulfuric acid solution, nitric acid solution, hydrofluoric acid solution and oxalic acid solution.

[0009] Preferably, the mass concentration of the acid solution is 5-20%; the mass-to-volume ratio of the quartz crucible powder to the acid solution is 1g:1-5mL; and the acid washing and impurity removal treatment time is 4-24h.

[0010] Preferably, in step (3), the mass ratio of the pure silicon powder to the silicon dioxide powder is 1:1.5~2.

[0011] Preferably, in step (3), the heating rate of the disproportionation reaction is 8~15℃ / min, and the temperature is maintained for 20~40min for every 300℃ increase. The final temperature of the disproportionation reaction is 1300~1400℃, and the holding time is 30~50min.

[0012] Preferably, in step (3), the cooling rate is 8~15℃ / min.

[0013] This invention provides a silicon suboxide prepared by the above-described method for preparing silicon suboxide using quartz crucible waste.

[0014] Preferably, the oxygen content in the silicon suboxide is 28-38 at.

[0015] The present invention also provides an application of the aforementioned silicon suboxide in lithium-ion battery anode materials.

[0016] The beneficial effects of this invention are: This invention transforms waste quartz crucibles generated in the photovoltaic industry into high-value-added silicon suboxide materials, turning waste into treasure and effectively alleviating the environmental pressure caused by the accumulation of waste crucibles. It can simultaneously digest photovoltaic silicon cutting waste and realize the synergistic resource utilization of various photovoltaic solid wastes. At the same time, the operating conditions of each step are mature, the equipment is highly versatile, and it is suitable for large-scale production.

[0017] The silicon suboxide prepared by this invention has an oxygen content of 28-38 at and a conversion rate of 90-98%, and can be used to prepare lithium-ion battery anode materials. Attached Figure Description

[0018] Figure 1 Here is a photograph of the silicon suboxide product prepared in Example 1; Figure 2SEM image of the silicon suboxide product prepared in Example 1; Figure 3 The image shows the XRD pattern of the silicon suboxide product prepared in Example 1. Figure 4 Electrochemical cycling diagram of the silicon suboxide prepared in Example 1 as a lithium-ion battery anode material. Detailed Implementation

[0019] This invention provides a method for preparing silicon suboxide using quartz crucible waste, comprising the following steps: (1) The quartz crucible waste is crushed, ground and sieved to obtain quartz crucible powder; (2) The quartz crucible powder is acid-washed to remove impurities, and silicon dioxide powder is obtained; (3) After mixing silica powder and pure silicon powder, disproportionation reaction is carried out and then cooled to obtain silicon suboxide.

[0020] In this invention, in step (1), the particle size of the quartz crucible powder is 2~5μm.

[0021] In this invention, the crushing is carried out using a jaw crusher, impact crusher, air jet mill, European-style impact crusher, or VSI vertical shaft impact crusher.

[0022] In this invention, in step (2), the acid washing and impurity removal process is carried out by soaking in an acid solution, wherein the acid solution includes one or more of hydrochloric acid solution, sulfuric acid solution, nitric acid solution, hydrofluoric acid solution and oxalic acid solution.

[0023] In this invention, the mass concentration of the acid solution is 5-20%, specifically 5%, 10%, 15%, or 20%; the mass-to-volume ratio of the quartz crucible powder to the acid solution is 1g:1-5mL; and the acid washing and impurity removal treatment time is 4-24h, specifically 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, or 24h.

[0024] In this invention, in step (3), the mass ratio of pure silicon powder to silicon dioxide powder is 1:1.5~2, preferably 1:1.6~2.0, and more preferably 1:1.8~2.0.

[0025] In this invention, in step (3), it is preferred to use a V-type mixer, a double cone mixer, a two-dimensional mixer, a three-dimensional motion mixer or an HJ series powder mixer for mixing.

[0026] In this invention, in step (3), the heating rate of the disproportionation reaction is 8~15℃ / min, specifically 8℃ / min, 10℃ / min, 12℃ / min, 14℃ / min, 15℃ / min; the holding time is 20~40min for every 300℃ increase, specifically 20min, 25min, 30min, 35min, 40min; the final temperature of the disproportionation reaction is 1300~1400℃, specifically 1300℃, 1320℃, 1340℃, 1350℃, 1380℃, 1400℃, and the holding time is 30~50min, preferably 40min.

[0027] In this invention, in step (3), the cooling rate is 8~15℃ / min, specifically 8℃ / min, 10℃ / min, 12℃ / min, 14℃ / min, or 15℃ / min.

[0028] This invention provides a silicon suboxide prepared by the above-described method for preparing silicon suboxide using quartz crucible waste.

[0029] In this invention, the oxygen content in the silicon suboxide is 28~38 at%.

[0030] The present invention also provides an application of the aforementioned silicon suboxide in lithium-ion battery anode materials.

[0031] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0032] Example 1

[0033] Waste quartz crucibles with a SiO2 content of 99% were crushed, ground, and sieved using a jaw crusher to obtain powder with a particle size of 2-5 μm. The powder was then soaked in a 10% hydrochloric acid solution for 10 hours at a solid-liquid ratio of 1 g:5 mL. After soaking, the powder was washed with water and dried to obtain silica powder. The pure silica powder and silica powder were mixed evenly in a V-type mixer at a mass ratio of 1:2. The mixed material was then transferred to a vacuum reactor for a disproportionation reaction. The heating rate was set at 10 °C / min, and the temperature was maintained for 30 minutes for every 300 °C increase. The temperature was increased to 1400 °C and maintained for 40 minutes. The disproportionation reaction generated silica vapor. The cooling rate of the condensation zone was set at 10 °C / min, and the silica vapor was gradually reduced to room temperature to produce silica product. The silica product had an oxygen content of 32 at% and a conversion rate of 93%.

[0034] from Figure 1As can be seen, the image is an optical photograph of the sample after high-temperature heat treatment. After high-temperature treatment, the raw material undergoes thermal decomposition, generating a large amount of black decomposition residue. The residue is piled up in the crucible in the form of flakes and fragments. The inner wall of the crucible shows obvious traces of thermal oxidation and carbonization, which directly reflects the macroscopic morphology and reaction state of the product after the high-temperature thermal reaction.

[0035] from Figure 2 It can be seen that the curve does not have sharp characteristic diffraction peaks, but only broadened diffuse bulges, indicating that the obtained product is mainly amorphous and amorphous, with almost no long-range ordered crystalline phase structure.

[0036] from Figure 3 It can be seen that the product consists of a large number of irregular particles of varying sizes, with distinct edges and corners, a wide size distribution, and the particles stacked on top of each other.

[0037] Example 2

[0038] Waste quartz crucibles with a SiO2 content of 99% were crushed, ground, and sieved using an impact crusher to obtain powder with a particle size of 2-5 μm. The powder was then soaked in a 15% sulfuric acid solution for 6 hours at a solid-liquid ratio of 1 g:4 mL. After soaking, the powder was washed with water and dried to obtain silica powder. The pure silica powder and silica powder were mixed evenly in a V-type mixer at a mass ratio of 1:2. The mixed material was then transferred to a vacuum reactor for a disproportionation reaction. The heating rate was set at 8 °C / min, and the temperature was maintained for 35 minutes for every 300 °C increase. The temperature was then raised to 1350 °C and maintained for 40 minutes. The disproportionation reaction generated silicon suboxide vapor. The cooling rate of the condensation zone was set at 8 °C / min, and the silicon suboxide vapor was gradually reduced to room temperature to produce a silicon suboxide product with an oxygen content of 34 at% and a conversion rate of 95%.

[0039] Example 3

[0040] Waste quartz crucibles with a SiO2 content of 99% were crushed, ground, and sieved using an air jet mill to obtain powder with a particle size of 2-5 μm. The powder was then soaked in a 5% nitric acid solution for 12 hours at a solid-liquid ratio of 1 g:3 mL. After soaking, the powder was washed with water and dried to obtain silica powder. The pure silica powder and silica powder were mixed evenly in a V-type mixer at a mass ratio of 1:2. The mixed material was then transferred to a vacuum reactor for a disproportionation reaction. The heating rate was set at 12 °C / min, and the temperature was maintained for 20 minutes for every 300 °C increase. The temperature was increased to 1320 °C and maintained for 45 minutes. The disproportionation reaction generated silicon suboxide vapor. The cooling rate of the condensation zone was set at 12 °C / min, and the silicon suboxide vapor was gradually reduced to room temperature to produce a silicon suboxide product with an oxygen content of 35 at% and a conversion rate of 92%.

[0041] Example 4

[0042] Waste quartz crucibles with a SiO2 content of 99% were crushed, ground, and sieved using an air jet mill to obtain powder with a particle size of 2-5 μm. The powder was then soaked in an 8% hydrofluoric acid solution for 8 hours at a solid-liquid ratio of 1 g:1 mL. After soaking, the powder was washed with water and dried to obtain silica powder. The pure silica powder and silica powder were mixed evenly in a V-type mixer at a mass ratio of 1:2. The mixed material was then transferred to a vacuum reactor for a disproportionation reaction. The heating rate was set at 14 °C / min, with a holding time of 30 min for every 300 °C increase, and a holding time of 40 min at 1380 °C. The disproportionation reaction generated silicon suboxide vapor. The cooling rate of the condensation zone was set at 14 °C / min, and the silicon suboxide vapor was gradually reduced to room temperature to produce a silicon suboxide product with an oxygen content of 33 at% and a conversion rate of 95%.

[0043] Example 5

[0044] Waste quartz crucibles with a SiO2 content of 99% were crushed, ground, and sieved using an air jet mill to obtain powder with a particle size of 2-5 μm. The powder was then soaked in a 12% oxalic acid solution for 24 hours at a solid-liquid ratio of 1 g:2 mL. After soaking, the powder was washed with water and dried to obtain silica powder. The pure silica powder and silica powder were mixed evenly in a V-type mixer at a mass ratio of 1:2. The mixed material was then transferred to a vacuum reactor for a disproportionation reaction. The heating rate was set at 15 °C / min, and the temperature was maintained for 25 minutes for every 300 °C increase. The temperature was then increased to 1400 °C and maintained for 50 minutes. The disproportionation reaction generated silica vapor. The cooling rate of the condensation zone was set at 15 °C / min, and the silica vapor was gradually reduced to room temperature to produce silica product. The silica product had an oxygen content of 36 at% and a conversion rate of 95%.

[0045] The silicon suboxide obtained in Example 1 was used as a negative electrode material for lithium-ion batteries. The specific preparation process is as follows: The silicon suboxide active material, conductive carbon black, and binder sodium alginate obtained in Example 1 were thoroughly mixed in deionized water at a mass ratio of 7:2:1 to prepare a negative electrode slurry. The slurry was coated on copper foil, dried, rolled, and cut to obtain the negative electrode sheet. A CR2032 coin cell was assembled in an argon glove box using lithium metal as the counter electrode; the electrolyte was 1 mol / L LiPF6. After the battery was allowed to stand, constant current charge-discharge cycle tests were performed at 0.5C and a voltage window of 0.01~1.5V. The test results are shown in [Figure number missing]. Figure 4 .from Figure 4It can be seen that the silicon suboxide anode has a first-cycle charging specific capacity of over 2600 mAh / g; after initial cycle activation, the coulombic efficiency remains stable at 98-100%; the charging specific capacity gradually decreases with cycling, and after 140 cycles, the charging specific capacity is approximately 850 mAh / g. The material has a high initial lithium storage capacity and is suitable for lithium-ion battery anodes.

[0046] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing silicon suboxide using quartz crucible waste, characterized in that, Includes the following steps: (1) The quartz crucible waste is crushed, ground and sieved to obtain quartz crucible powder; (2) The quartz crucible powder is acid-washed to remove impurities, and silicon dioxide powder is obtained; (3) After mixing silica powder and pure silicon powder, disproportionation reaction is carried out and then cooled to obtain silicon suboxide.

2. The method for preparing silicon suboxide using quartz crucible waste according to claim 1, characterized in that, In step (1), the particle size of the quartz crucible powder is 2~5μm.

3. The method for preparing silicon suboxide using quartz crucible waste according to claim 1 or 2, characterized in that, In step (2), the acid washing and impurity removal process involves soaking in an acid solution, wherein the acid solution includes one or more of hydrochloric acid solution, sulfuric acid solution, nitric acid solution, hydrofluoric acid solution and oxalic acid solution.

4. The method for preparing silicon suboxide using quartz crucible waste according to claim 3, characterized in that, The mass concentration of the acid solution is 5-20%; the mass-to-volume ratio of the quartz crucible powder to the acid solution is 1g:1-5mL; and the acid washing and impurity removal treatment time is 4-24h.

5. The method for preparing silicon suboxide using quartz crucible waste according to claim 2 or 4, characterized in that, In step (3), the mass ratio of pure silicon powder to silicon dioxide powder is 1:1.5~2.

6. The method for preparing silicon suboxide using quartz crucible waste according to claim 5, characterized in that, In step (3), the heating rate of the disproportionation reaction is 8~15℃ / min, and the temperature is maintained for 20~40min for every 300℃ increase. The final temperature of the disproportionation reaction is 1300~1400℃, and the holding time is 30~50min.

7. The method for preparing silicon suboxide using quartz crucible waste according to claim 6, characterized in that, In step (3), the cooling rate is 8~15℃ / min.

8. The silicon suboxide prepared by the method for preparing silicon suboxide using quartz crucible waste as described in any one of claims 1 to 7.

9. The silicon suboxide according to claim 8, characterized in that, The oxygen content in the silicon suboxide is 28~38 at.

10. The application of silicon suboxide as described in claim 8 or 9 in lithium-ion battery anode materials.